Evaluation of Inclusive Education Program at Elementary Schools - Nuroel Tri Isna Wijaya; Ruqaiyah Ruqaiyah; Siti Zulaikha (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study is to describe the program's effectiveness using a qualitative descriptive method by examining the context, input, process, and product of an inclusive education program at an elementary school in Palembang. Interviews, observation, documentation, questionnaires, and focus group discussions are all used to collect data. The principal, deputy principal for curriculum, the education office of Palembang city, class teachers, the South Sumatera Provincial Education Office, and Guardians of Special Needs Students served as informants for the research. The findings indicated that the contextual evaluation did not consider the program's needs and objectives. There are flaws in the way organizers and implementers analyze program needs in terms of context. The outcome of the input evaluation indicates that it is not adhering to the components of inclusive education implementation. The process evaluation revealed that the performance adhered to child-friendly schools in some areas, most notably in implementing the teaching and learning process. While some product evaluation results have been successful, critical considerations must be significantly improved, beginning with program planning, monitoring, and reporting. In general, the program evaluation components indicate that schools have demonstrated a high level of commitment and consistency in implementing the program since 2013. This needs to be improved by the guidelines for inclusive education implementation.